English Teachers’ Attitudes Towards Professional Development Activities - Kshetree, Arun Kumar; Pokhrel, Prem Raj; KC, Kamala (Lumbini Journal of Language and Literature, 2024)
The role of teachers extends beyond the classroom; they are pivotal change agents in society who must continuously update their knowledge and skills to align with evolving time, technology and circumstances. This article explores some of the most common and effective strategies for teacher learning and professional development and teachers' attitudes toward them. For this, a questionnaire was administered to purposively selected thirty English teachers teaching grades XI and XII in government schools in and around Butwal. This study sheds light on the practices adopted by teachers and the degree to which they embrace professional development opportunities. The findings aim to provide actionable insights for fostering a culture of continuous learning among educators. Though most of the strategies and activities presented in this article do not cost extra fund, many teachers are not aware of the processes and opportunities of teacher learning and professional development. They are not trying these activities in their day to day English language teaching and learning situations. Knowing the importance of the activities and opportunities of professional learning and development, the teachers do not using them to be updated to teach in their ELT classes. This ultimately seems to hamper the quality of teaching and education process as well as the personality of the teachers due to being less competent in teaching English.